Altered relationship between electrophysiological response to errors and gray matter volumes in an extended network for error‐processing in pediatric obsessive‐compulsive disorder. Issue 4 (18th February 2013) - Liu, Yanni; Hanna, Gregory L.; Carrasco, Melisa; Gehring, William J.; Fitzgerald, Kate D.
<x xml:space="preserve">Abstract</x> Pediatric patients with obsessive‐compulsive disorder (OCD) show an increased electrophysiological response to errors that is thought to be localized to the posterior medial prefrontal cortex (pMFC). However, the relation of this response, the error‐related negativity (ERN), to underlying brain structures remains unknown. In an examination of 20 pediatric OCD patients and 20 healthy youth, we found that more negative ERN amplitude was correlated with lower gray matter (GM) density in pMFC and orbital frontal cortex. The association of the ERN with pMFC gray matter volume was driven by the patient group. In addition, a group difference in the association of ERN with gray matter in right insula was observed, showing an association of these measures in healthy youth (more negative ERN amplitude was associated with lower GM density in insula), but not in patients. These findings provide preliminary evidence linking gray matter volumes in an extended network for error processing to the ERN, and suggest that structural alterations in this network may underlie exaggeration of the ERN in pediatric OCD. Hum Brain Mapp 35:1143–1153, 2014. © 2013 Wiley Periodicals, Inc.